Beethoven in Russia music and politics - Skinner, Frederick W. (Indiana University Press, 2022)
-- The author is an emeritus professor in the Department of History at the University of Montana. -- Beethoven is arguably the most well-recognized composer and continues to fascinate both scholars and general readers alike. This work explores the ways in which Russian and Soviet political leaders used Beethoven's music as tool and propaganda for their own agendas. -- The work adds to the IU Press list in its fit across several key publishing areas, including the excellent Russian Music Studies series, our lists of titles in Russian history, culture, and politics, and our extensive list of titles on the cultural politics of propaganda in Europe and Russia. -- The audience is scholars of Russian history, Russian music, those who work on culture and propaganda theory, and general readers interested in Beethoven and the history of Russia. While the work is long, the text is written in an engaging style with clear language throughout.